PENGARUH KINERJA PEREKONOMIAN TERHADAP KUALITAS LINGKUNGAN HIDUP DI INDONESIA - Astrid Maria Esther; Agustina Suparyati (Media Ekonomi, 2023)
The purpose of this study is to analyze the impact of economic performance which consists of growth in per capita income, Human Development Index, Public Consumption Expenditure, and Poverty Level on Environmental Quality in Indonesia (EQI). This study focuses on 34 provinces in Indonesia from 2016 to 2020 using the panel data analysis method. Data was obtained from the Statistics Processing Agency (BPS) and Bank Indonesia (BI). The regression results show that economic growth, public consumption spending, and the poverty rate do not affect the environmental quality index and only the Human Development Index which has a positive effect on environmental quality, especially from the high education component forming a society that is intellectually educated and has a lifestyle that is influential in terms of consumption of environmentally friendly products.